2019
DOI: 10.7554/elife.49253
|View full text |Cite
|
Sign up to set email alerts
|

A potent voltage-gated calcium channel inhibitor engineered from a nanobody targeted to auxiliary CaVβ subunits

Abstract: Inhibiting high-voltage-activated calcium channels (HVACCs; CaV1/CaV2) is therapeutic for myriad cardiovascular and neurological diseases. For particular applications, genetically-encoded HVACC blockers may enable channel inhibition with greater tissue-specificity and versatility than is achievable with small molecules. Here, we engineered a genetically-encoded HVACC inhibitor by first isolating an immunized llama nanobody (nb.F3) that binds auxiliary HVACC CaVβ subunits. Nb.F3 by itself is functionally inert,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 62 publications
(81 reference statements)
0
29
0
1
Order By: Relevance
“…One of these nanobodies, termed nb.F3, bound all four Ca V β isoforms when expressed in cells (Morgenstern et al . 2019), which was not surprising given the high homology among these auxiliary subunits in their conserved src homology 3 (SH3) and guanylate kinase (GK) domains (Chen et al . 2004; Opatowsky et al .…”
Section: Voltage‐gated Calcium Channels: Basic Structure Function Anmentioning
confidence: 99%
See 3 more Smart Citations
“…One of these nanobodies, termed nb.F3, bound all four Ca V β isoforms when expressed in cells (Morgenstern et al . 2019), which was not surprising given the high homology among these auxiliary subunits in their conserved src homology 3 (SH3) and guanylate kinase (GK) domains (Chen et al . 2004; Opatowsky et al .…”
Section: Voltage‐gated Calcium Channels: Basic Structure Function Anmentioning
confidence: 99%
“…3 and ) (Morgenstern et al . 2019). Whole‐cell patch clamp experiments demonstrated that nb.F3‐Nedd4L essentially eliminated reconstituted Ca V 1.2, Ca V 1.3 and Ca V 2.1‐Ca V 2.3 channel currents (Fig.…”
Section: Voltage‐gated Calcium Channels: Basic Structure Function Anmentioning
confidence: 99%
See 2 more Smart Citations
“…En relación a NeDD4, recientemente Morgenstern y colaboradores han diseñado un inhibidor recombinante en base a dicha proteína partiendo de la interacción entre Ca V β y NeDD4 reportada previamente. Con dicho inhibidor han logrado impedir la interacción física entre las subunidades Ca V α 1 de los HVA en forma selectiva y consecuentemente la funcionalidad de dichos canales (Morgenstern et al, 2019). Nuevos experimentos son necesarios para concluir acerca de los efectores moleculares que median el efecto de la actividad constitutiva de GHSR sobre el tráfico de los Ca V.…”
Section: Discusión Iunclassified